2017
DOI: 10.1042/bsr20170772
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid inhibits nasopharyngeal cancer cell proliferation and invasion via activation of FRα/ERK1/2/TSLC1 pathway

Abstract: Folic acid (FA), which is necessary for normal cell division of mammals, has been implicated to be involved in many tumors. Dietary FA intake has been reported to be associated with a lower risk of nasopharyngeal cancer (NPC). However, the molecular mechanisms of FA in NPC cells remain unclear. In the present study, we found that FA treatment dose dependently inhibited the proliferation, invasion and migration of NPC cells, via folate receptor α (FRα). We further found that FA, bound to FRα, induced the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Growing evidence has demonstrated that the activation of the ERK1/2 pathway accelerated the proliferation of tumor cells, including oral cancer [23], nasopharyngeal cancer [24], and hepatoma cells [25]. In this analysis, our findings revealed that overexpression of TRIM11 promoted the activation of the ERK1/2 signaling pathway in OS cells.…”
Section: Discussionsupporting
confidence: 53%
“…Growing evidence has demonstrated that the activation of the ERK1/2 pathway accelerated the proliferation of tumor cells, including oral cancer [23], nasopharyngeal cancer [24], and hepatoma cells [25]. In this analysis, our findings revealed that overexpression of TRIM11 promoted the activation of the ERK1/2 signaling pathway in OS cells.…”
Section: Discussionsupporting
confidence: 53%
“…In another study, folate deprivation enhanced invasiveness of colon cancer cells through the activation of sonic hedgehog and NF-κB signaling [48]. Inhibitory effects of folic acid on metastasis and proliferation have been also linked to the activation of the folate receptor-ERK1/2-TSLC1 signaling pathway [49]. Contrary to these studies, we have previously reported that folate deprivation inhibits migration and invasion of cultured cancer cells and decreases tumor growth and metastasis in a mouse model [28,42,50].…”
Section: Introductionmentioning
confidence: 95%
“…The same observation was obtained previously when empty FA-DABA-SMA was applied to the PANC-1 cells caused a decrease in cell proliferation ( Figure 5 ). To explain these observations, other studies have reported that the binding of folic acid to its receptor can mediate a downstream signalling cascade that is able to inhibit the cellular survival processes including cell proliferation [ 28 , 29 ]. Our data are consistent with these reports.…”
Section: Resultsmentioning
confidence: 99%